Genomics of Flower Identity in Grapevine (Vitis vinifera L.) - Palumbo, Fabio; Vannozzi, Alessandro; Magon, Gabriele; Lucchin, Margherita; Barcaccia, Gianni (Frontiers in Plant Science, 2019)
The identity of the four characteristic whorls of typical eudicots, namely, sepals, petals, stamens, and carpels, is specified by the overlapping action of homeotic genes, whose single and combined contributions have been described in detail in the so-called ABCDE model. Continuous species-specific refinements and translations resulted in this model providing the basis for understanding the genetic and molecular mechanisms of flower development in model organisms, such as Arabidopsis thaliana and other main plant species. Although grapevine (Vitis vinifera L.) represents an extremely important cultivated fruit crop globally, studies related to the genetic determinism of flower development are still rare, probably because of the limited interest in sexual reproduction in a plant that is predominantly propagated asexually. Nonetheless, several studies have identified and functionally characterized some ABCDE orthologs in grapevine. The present study is intended to provide a comprehensive screenshot of the transcriptional behavior of 18 representative grapevine ABCDE genes encoding MADS-box transcription factors in a developmental kinetic process, from preanthesis to the postfertilization stage and in different flower organs, namely, the calyx, calyptra, anthers, filaments, ovary, and embryos. The transcript levels found were compared with the proposed model for Arabidopsis to evaluate their biological consistency. With a few exceptions, the results confirmed the expression pattern expected based on the Arabidopsis data.